Controlled Dip Reactor Design to Increase Bakterioselulosa Produce Based on ATMega8535 Microcontroller - Amri, Rahyul (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Contact with O2 and at the same time ability to absorbent of nutrient will be very determining of productivity level of bakterioselulosa. On that account, for the scale up production, there are some done efforts, like Rotary Disc Reactor (RDR), as developed by Norhayati [1]. The RDR is unable to rotate less than 7 rpm (equivalent 10 second to every rotation). At this research, weakness of the rotary disk bioreaktor was overcome by developing Controlled Dip Reactor (CDR). Excess of proposed appliance is user can arrange the the duration submerged phase in growth liquid medium and exposed to the air phase as according to experiment design, so that more effective and be free to to gain time optimum to each the phase utilize to get maximal production of bakterioselulosa. At the testing, designed appliance can lift place grow medium of bakterioselulosa toward as high as 15 cm meaning exposed to the air,and degrade place grow of bakterioselulosa medium downwards until 1 cm measured from medium place base, which mean bakterioselulosa submerged liquid of the growth medium and the time exposed to the air and exposed to the liquid can be controlled to vary from 1 until 20 minute.